2021
DOI: 10.1038/s41390-021-01832-9
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and sex-dependent effects of phlebotomy-induced anemia on the neonatal mouse hippocampal transcriptome

Abstract: Background: Phlebotomy-induced anemia (PIA) is universal and variable in degree among preterm infants and may contribute to neurodevelopmental risk. In mice, PIA causes brain tissue hypoxia, iron deficiency, and long-term sex-dependent neurobehavioral abnormalities. The neuroregulatory molecular pathways disrupted by PIA underlying these effects are unknown. Methods: Male and female pups were phlebotomized daily from postnatal day (P)3-P14 via facial venipuncture to tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
(67 reference statements)
3
15
0
Order By: Relevance
“…By assessing global changes in hippocampal gene expression, this study presents novel findings pertaining to long-term sex-specific hippocampal effects of early-life ID and prenatal choline supplementation on gene regulation and changes in pre-defined neurologic biomarkers. Consistent with our previous findings in a neonatal model of PIA (8), substantially more gene expression changes in the hippocampal transcriptome were found in female than male rodents, indicating a more robust gene regulatory response to early-life ID in female rats. Prenatal choline supplementation, a promising adjunct therapy that prevents some long-term behavioral abnormalities following early-life ID, led to even more DEGs in both sexes of iron-sufficient compared to iron-deficient groups, further supporting previous observations of the interaction between choline and iron status in regulating hippocampal gene expression (25, 28).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…By assessing global changes in hippocampal gene expression, this study presents novel findings pertaining to long-term sex-specific hippocampal effects of early-life ID and prenatal choline supplementation on gene regulation and changes in pre-defined neurologic biomarkers. Consistent with our previous findings in a neonatal model of PIA (8), substantially more gene expression changes in the hippocampal transcriptome were found in female than male rodents, indicating a more robust gene regulatory response to early-life ID in female rats. Prenatal choline supplementation, a promising adjunct therapy that prevents some long-term behavioral abnormalities following early-life ID, led to even more DEGs in both sexes of iron-sufficient compared to iron-deficient groups, further supporting previous observations of the interaction between choline and iron status in regulating hippocampal gene expression (25, 28).…”
Section: Discussionsupporting
confidence: 91%
“…In the formerly ID male rats, activation of ESR1 is a novel discovery and may have a role in reducing hippocampal-dependent cognitive impairment (32,33). These male-specific effects on gene regulators could explain the sex-specific cognitive impairments associated with the interaction between early-life neuroinflammation and iron status in both preclinical models and human infants (7,8,34,35). In the formerly ID female rats, activation of FOXO3 and MECP2 gene network could improve the overall metabolic activity and neuronal differentiation via recruitment of relevant target genes, including EGR4, FOS, ENO2, and NPAS4, thereby compensating for the reduced capacity of iron-mediated cellular metabolism (36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the use of such low haemoglobin thresholds in 22% of units are unclear but may represent an underestimation of transfusion threshold, as we had to use wide ranges for several clinical scenarios as described previously (online supplemental table S1). Without further clinical trials, it is not known whether these low haemoglobin thresholds are safe for neonates, as various preclinical studies have suggested adverse outcomes following prolonged severe anaemia 21–23…”
Section: Discussionmentioning
confidence: 99%
“…Without further clinical trials, it is not known whether these low haemoglobin thresholds are safe for neonates, as various preclinical studies have suggested adverse outcomes following prolonged severe anaemia. [21][22][23]…”
Section: Comparison With Rbc Trialsmentioning
confidence: 99%